2015
DOI: 10.1111/jen.12246
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional variations at Nesidiocoris tenuis feeding sites and reciprocal interactions between the mirid and tomato plants

Abstract: Nesidiocoris tenuis (Reuter) (Hemiptera: Miridae) uses a flush‐and‐lacerate feeding strategy producing necrotic rings (NR) at feeding sites in tomato plants. The aim was to investigate the variation in the concentrations of amino acids (aa) and sugars at feeding sites, and its effect on this mirid's life‐history traits and behaviour. The concentration of nutrients was measured in different parts of stems damaged by N. tenuis and mechanically using liquid chromatography. aa concentrations increased below NR; ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
(171 reference statements)
2
11
0
Order By: Relevance
“…Besides, their perfomance varies greatly with the mirid species, host plant, the availability of alternative host plant, and even the plant part (McGregor et al, 2000;Perdikis and Lykouressis, 2000;Lucas and Alomar, 2001;Wheeler, 2001;Sanchez et al, 2004;Biondi et al, 2016). In the most favorable cases, plant feeding allows the insect to complete its development and reproduce but, generally, the nymphal stage lasts much longer and egg-laying is very limited in comparison to when feeding on prey (Naranjo and Gibson, 1996;Perdikis and Lykouressis, 2000;Sanchez et al, 2004Sanchez et al, , 2016Urbaneja et al, 2005;Perdikis et al, 2007;Lykouressis et al, 2008;Ingegno et al, 2011;Mollá et al, 2014). In consequence, omnivorous mirids consume primarily prey when available and phytophagy, as well as plant injury, increases exponentially when animal food is scarce (Sanchez, 2008(Sanchez, , 2009Sanchez and Lacasa, 2008;Calvo et al, 2009;Arnó et al, 2010;Sanchez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, their perfomance varies greatly with the mirid species, host plant, the availability of alternative host plant, and even the plant part (McGregor et al, 2000;Perdikis and Lykouressis, 2000;Lucas and Alomar, 2001;Wheeler, 2001;Sanchez et al, 2004;Biondi et al, 2016). In the most favorable cases, plant feeding allows the insect to complete its development and reproduce but, generally, the nymphal stage lasts much longer and egg-laying is very limited in comparison to when feeding on prey (Naranjo and Gibson, 1996;Perdikis and Lykouressis, 2000;Sanchez et al, 2004Sanchez et al, , 2016Urbaneja et al, 2005;Perdikis et al, 2007;Lykouressis et al, 2008;Ingegno et al, 2011;Mollá et al, 2014). In consequence, omnivorous mirids consume primarily prey when available and phytophagy, as well as plant injury, increases exponentially when animal food is scarce (Sanchez, 2008(Sanchez, , 2009Sanchez and Lacasa, 2008;Calvo et al, 2009;Arnó et al, 2010;Sanchez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the most favorable cases, plant feeding allows the insect to complete its development and reproduce but, generally, the nymphal stage lasts much longer and egg-laying is very limited in comparison to when feeding on prey (Naranjo and Gibson, 1996;Perdikis and Lykouressis, 2000;Sanchez et al, 2004Sanchez et al, , 2016Urbaneja et al, 2005;Perdikis et al, 2007;Lykouressis et al, 2008;Ingegno et al, 2011;Mollá et al, 2014). In consequence, omnivorous mirids consume primarily prey when available and phytophagy, as well as plant injury, increases exponentially when animal food is scarce (Sanchez, 2008(Sanchez, , 2009Sanchez and Lacasa, 2008;Calvo et al, 2009;Arnó et al, 2010;Sanchez et al, 2016). Injuries produced by omnivorous mirids vary with the organ affected, and with the plant and mirid species.…”
Section: Introductionmentioning
confidence: 99%
“…In tomatoes, repetitive insertion of the stylet on vascular tissue induces necrotic rings on stems, leaves or flower petioles that may reduce plant vigour or cause flower abortion (El-Dessouki et al, 1976). Recently, Sánchez et al (2016), observed feeding activity of N. tenuis to produce a significant variation in the concentration and distribution of assimilates (i.e. amino acids and sugars) in tomato stems.…”
Section: Plant Damage By Mirid Predatorsmentioning
confidence: 99%
“…amino acids and sugars) in tomato stems. This chemical change in tomato was observed to inhibit the transfer of nutrients in the phloem and negatively affect the fitness of nymphs that develop on those parts of the plant (Sánchez et al, 2016). The intensity of injuries on tomato crops is proportional to the availability of the prey (Arnó et al, 2010a;Calvo et al, 2009b).…”
Section: Plant Damage By Mirid Predatorsmentioning
confidence: 99%
See 1 more Smart Citation